Methodology of problematization in medical courses: a pedagogical experience (Research, Society and Development, 2020)
The objective of this article was describe the pedagogical experiences in the module “Integration, Teaching and Community Service Practices” at the State University of Feira de Santana in Brazil (PIESC I-UEFS). It´s a qualitative study, carried out in a group of students of the first year of the medical course, the data were collected with participant observation and field notes. For the development of the course contents, the methodological approach of problematization was used through the Arc de Maguerez, the contextualization of knowledge was carried out in a Family Health unit, the dynamics of the course consisted of an alternation of theory and practice. The results of the experience materialized in the elaboration of a smart map of the epidemiological profile of the community and presentation of the results to the community. The evaluation of the learning experience in the integration of the curricular contents of the course with the health problems of the community was evaluated as positive by the students, community agents and other health professionals. In conclusion, the methodology of problematization, stimulated the protagonism, creativity and autonomy of the students, so that the strategies used have the potential to contribute to the training of doctors who overcome the vision of traditional medicine, it promotes the necessary competencies in the students so that in the future they become participatory medical professionals committed to social transformation.Incluir o resumo em inglês.